Serbia - Right-Sizing the Government Wage Bill - World Bank (World Bank, 2012)
Serbia's public sector wage bill constitutes a significant share of total government expenditure. At present, it is significantly higher than in most neighboring European Union (EU) member countries. This is largely due to higher average levels of compensation, rather than higher levels of staffing. While wage spending has fallen recently this is not the occasion to be sanguine about the Government's wage and employment policies. There are two reasons. First, continuing control over the wage bill is a key part of the Government's overall deficit reduction strategy. Given the Government's reluctance to raise taxes and the difficulty it confronts in reducing other major categories of expenditures (particularly pensions), restraining the wage bill is critical to fiscal sustainability. In connection with its standby arrangement with the International Monetary Fund (IMF), the government is committed to enacting fiscal responsibility legislation which would cap wage bill spending at eight percent of gross domestic product (GDP) over the medium term. To date, the Government has been relying on blunt instruments to achieve this target; most importantly a freeze on nominal wages and a partial freeze on the creation of new positions, both introduced in 2009. As the current recession eases, pressures to increase wages are mounting. The wage freeze is becoming politically unsustainable. More nuanced methods of restraining the wage bill are required. Second, over the longer term, the present policy of continuous wage and position freezes would undermine the quality of public administration. Persistent wage freezes would make it difficult to attract and retain competent staff. Persistent position freezes would lock in existing patterns of over- and under staffing. On the other hand, a reversion to the former system of ad hoc adjustments in staffing and wages could set the stage for unsustainable wage bill growth in the future. Structural reforms are therefore required.